The Paediatric Cataract Register (PECARE): an overview of operated childhood cataract in Sweden and Denmark. Issue 1 (14th June 2017) - Magnusson, Gunilla; Haargaard, Birgitte; Basit, Saima; Lundvall, Anna; Nyström, Alf; Rosensvärd, Annika; Tornqvist, Kristina
Abstract: Aim: To report basic epidemiological data concerning surgically treated childhood cataract in Sweden and Denmark. Methods: Data were derived from the Paediatric Cataract Register (PECARE), a binational, web‐based surgical register representing Sweden and Denmark. All children operated before 8 years of age between 1 January 2007 and 31 December 2013 were included. Age‐specific prevalence per 100 000 population was calculated. Results: A total 574 operations in 213 boys (51.7%) and 199 girls (48.3%), altogether 412 children, were registered, the vast majority ( n  =   395/412; 95.9%) being individuals with congenital/infantile cataract. Of these 412, a total of 294 (147 boys and 147 girls) were Swedish and 118 (66 boys and 52 girls) were Danish. The age‐specific prevalence of operated cataract in Sweden was 31/100 000 and in Denmark 28/100 000. In 454 of 574 eyes (79.1%), the cataract was dense. Altogether, 266 of 574 (46.3%) were operated during the first year of life, 193 during the first 12 weeks representing 33.6% of all operations. A primary intraocular lens (IOL) implantation was done in altogether 411 of 574 eyes (71, 6%). In total, 210 unilateral cataract operations (210/574; 36.6%) were performed. Persistent fetal vasculature (PFV) was present in 64 of 193 (33.1%) of those with a congenital unilateral cataract. In 84 individuals (84/395; 21.3%) with congenital or infantile cataract, a coexisting disorder was found. Conclusion: The age‐specific binational prevalence of operated congenital/infantile cataract in Sweden and Denmark is 30/100 000. About half of the operations are performed within the first year of life, one‐third within the first 3 months. In our study population, a primary IOL was implanted in the majority of cases.